Adversity Quotient, Leadership Resilience, and Mentoring and Coaching Strategies of Instructional Leaders - Tipolo, Mary Jane (Journal of Interdisciplinary Perspectives, 2024)
To improve the technical assistance strategy, this study evaluated the adversity quotient, leadership resilience, and mentoring and coaching techniques of instructional leaders. Respondents of this study were the 138 public secondary instructional leaders composed of department heads and master teachers chosen randomly from the 210 total population of department heads and master teachers in SDO, Iloilo City. Ethical factors were considered to achieve this overall goal. Respondents were informed of the study's objective, benefits, and risks before being requested for consent to participate as respondents in the survey. The 2012 Data Privacy Act maintained the confidentiality of the respondent’s identity. A descriptive research design with stratified random sampling examined demographic variables such as sex, designation, educational attainment, and length of service. The sample showed a notable sex disproportion, with most respondents being Master Teachers I, holding advanced degrees, and having over ten years of experience. Regarding sex, designation/position, and educational attainment of instructional leaders, there was no significant difference in the level of AQ® among respondents. However, there is a significant difference in the AQ® level of the respondents when grouped by their length of service. Additionally, AQ® analysis revealed "below average" levels for males and females, with significant differences across designations but not by educational attainment. Respondents with less experience showed "higher" resilience than those with longer tenures, while leadership resilience remained consistently high across all demographics. No significant differences were found in mentoring and coaching strategies based on the demographic profile. The findings suggest a need for targeted interventions to improve resilience among more experienced leaders and support more effective mentoring and coaching strategies. These insights inform the creation of a technical assistance plan to enhance instructional leadership.